Curcumin inhibits apoptosis by modulating Bax/Bcl-2 expression and alleviates oxidative stress in testes of streptozotocin-induced diabetic rats - Zhao L; Gu Q; Xiang L; Dong X; Li H; Ni J; Wan L; Cai G; Chen G (Dove Medical Press, 2017)
Lingling Zhao,1,2 Qianru Gu,2 Lanting Xiang,2 Xidan Dong,2 Huimin Li,2 Jinyao Ni,2 Li Wan,2 Guoping Cai,2 Guorong Chen2 1Department of Pathology, Zhejiang Provincial Hospital of TCM, Hangzhou, 2Department of Pathology, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, People’s Republic of China Scope: The present study was designed to examine the damage caused by high-fat diet and streptozotocin-induced diabetes on the testis of rats and the effects of curcumin against oxidative stress and apoptosis from high-fat diet and diabetes. Methods: Diabetes was induced by intraperitoneal injection of streptozotocin (30 mg/kg in 0.1 M sodium citrate buffer, pH 4.5) in obese rats. The rats in the obese and diabetic groups were treated with a daily dose of curcumin by intragastric intubation (100 mg/kg body weight) for 8 weeks. Testis tissue sections were stained with hematoxylin–eosin, and apoptosis was identified in situ by using terminal deoxynucleotidyl transferase dUTP nick end labeling. Results: Curcumin treatment improved the histological appearance of the testis and significantly reduced the apoptosis level in the testicular cells of the obese and the diabetic rats. The expression of proliferating cell nuclear antigen (PCNA) was restored in the testis tissues of diabetic rats at the end of curcumin treatment. Molecular analysis demonstrated that curcumin treatment significantly and simultaneously decreased Bax and increased Bcl-2 expressions, therefore elevating the ratio of Bcl-2/Bax. Furthermore, curcumin treatment significantly decreased malondialdehyde (MDA) and increased superoxide dismutase (SOD) levels in testis tissue samples of the diabetic rats. Conclusion: Curcumin treatment preserved the morphology of testes; restored the expression of PCNA, MDA, and SOD; and inhibited testicular cell death in diabetic rats. The capability of curcumin in inhibiting oxidative stress and modulating the Bax/Bcl-2-mediated cell death pathway reveals its potential as a therapeutic agent against diabetes. Keywords: apoptosis, curcumin, diabetes, oxidative stress, testis